2016
DOI: 10.1371/journal.pone.0149331
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the mir-15a/16-1 Loci Impairs Its Processing and Augments B-1 Expansion in De Novo Mouse Model of Chronic Lymphocytic Leukemia (CLL)

Abstract: New Zealand Black (NZB) mice, a de novo model of CLL, share multiple characteristics with CLL patients, including decreased expression of miR-15a/16-1. We previously discovered a point mutation and deletion in the 3' flanking region of mir-16-1 of NZB and a similar mutation has been found in a small number of CLL patients. However, it was unknown whether the mutation is the cause for the reduced miR-15a/16-1 expression and CLL development. Using PCR and in vitro microRNA processing assays, we found that the NZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…In order to study the effects of the miR-15a/16-1 deficiency on the mouse B cell development the congenic mice were generated by consecutive crossbreeding wild type DBA and CLL mouse model NZB mice with mutant mir-15a/16-1 selection. The resultant strain termed DBA −/− was used for aging followed by further analysis [ 9 ]. First, we found that the level of miR-15a was decreased in both B1 and B2 cells derived from NZB and DBA congenics (DBA −/− ) when compared to the wild-type DBA (Figure 1A ), which positively correlated with Dleu2 levels in splenocytes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to study the effects of the miR-15a/16-1 deficiency on the mouse B cell development the congenic mice were generated by consecutive crossbreeding wild type DBA and CLL mouse model NZB mice with mutant mir-15a/16-1 selection. The resultant strain termed DBA −/− was used for aging followed by further analysis [ 9 ]. First, we found that the level of miR-15a was decreased in both B1 and B2 cells derived from NZB and DBA congenics (DBA −/− ) when compared to the wild-type DBA (Figure 1A ), which positively correlated with Dleu2 levels in splenocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, no difference in B1P levels was observed in younger animals suggesting that this is an age-associated phenomenon (data not shown). Recently, we have shown that DBA congenic animals exhibit an increased percentage of lineage − sca1 + c-kit + (LSK) cells in DBA −/− congenic mice [ 9 ]. To test their ability to give rise to B lineage cells, LSK progenitors derived from the DBA, NZB and DBA −/− mice bone marrow were differentiated in vitro under conditions favoring B cell development.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, in our subset of patients, the RPIII-mediated transcription of miR-15a and miR-16-1 was associated with a poor prognostic marker of CLL [ 115 ]. The 13q14 deletion is not the only cause of the miR-15a and miR-16-1 down-regulation: for instance, a point mutation downstream the miR-16-1 in the New Zealand Black (NZB) CLL mouse models affects the processing of primiR-15a/16-1 to pre-miR-15a/16-1 , thus leading to decreased expression of those miRNAs [ 116 ]. A common pathogenic pathway that link miR-15a/16-1 cluster, miR-34b/c cluster and tumor protein p53 with 13q, 11q, and 17p deletion has been reported in CLL.…”
Section: Mirnas In Hematological Malignanciesmentioning
confidence: 99%